Molecular profiling and prevalence of hepatitis B virus (HBV) in clinical isolates and its importance - Parashar, Vatsal; Raina, Dimple; Sahni, Shweta (The Scientific Temper, 2023)
Hepatitis B virus (HBV) DNA quantification provides insight for treating and curing HBV and hepatic cell carcinoma (HCC). This study deals with the molecular profiling of HBV DNA viral load and the molecular investigation of the HBV DNA genotypes (Revill et al., 2019). The distribution of various genotypes among the population has been studied in this research. Total 102 EDTA serum samples were taken from suspected HBV reactive patients from the different Departments, including OPDs and IPDs of Shri Mahant Indresh Hospital, Dehradun, Uttarakhand, India. After DNA extraction real-time quantification was performed. Nested PCR technology did the HBV genotypic characterization. Out of 102 samples collected for the serological test, 60 samples were found positive for HBsAg and further biochemical profiling was performed. The HBV viral load was quantified in the samples and their titer values were observed between 34 IU/mL to 1.10×108 IU/mL in which, 16.7% (10 cases) were in which the target was not detected and 83.3%, i.e., 50 cases were with high viral load. Then genotyping of these 50 samples with high viral load was performed by Nested PCR. Genotype d of HBV was found to be most prevalent in 65.62% of cases i.e. 32 cases in total. The presence of HBV genotype varies within the different geographical conditions because of the differences in the major causative factors.